Mechanosensitive channel Piezo1 in calcium dynamics: structure, function, and emerging therapeutic strategies - Liu, Yu; Xu, Yu-Qiu; Long, Yu-Yin; Xiao, Hui; Ma, Yu-Ying; Li, Yong-Wang (Frontiers in Molecular Biosciences, 2025)
Piezo1, a trimeric mechanosensitive cation channel discovered in 2010 and recognized with the 2021 Nobel Prize for its seminal role in mechanotransduction, has emerged as a key transducer of mechanical forces into calcium ions (Ca2+) signaling. Its distinctive propeller-like structure confers high mechanosensitivity, enabling rapid and graded Ca2+ influx under diverse mechanical stimuli such as shear stress, stretch, or compression. This Ca2+ entry establishes localized nanodomains and amplifies signals via Ca2+-induced Ca2+ release, thereby activating a spectrum of downstream effectors including CaMKII, NFAT, and YAP/TAZ. Through these pathways, Piezo1 orchestrates critical physiological processes including vascular tone, skeletal remodeling, immune responses, neural plasticity, and organ development. Conversely, its dysregulation drives numerous pathologies, ranging from hypertension and atherosclerosis to neurodegeneration, fibrosis, osteoarthritis, and cancer. Advances in pharmacological modulators (e.g., Yoda1, GsMTx4), gene-editing, and nanomedicine underscore promising therapeutic opportunities, though challenges persist in tissue specificity, off-target effects, and nonlinear Ca2+ dynamics. This review synthesizes current knowledge on Piezo1-mediated Ca2+ signaling, delineates its dual roles in physiology and disease, and evaluates emerging therapeutic strategies. Future integration of structural biology, systems mechanobiology, and artificial intelligence is poised to enable precision targeting of Piezo1 in clinical practice.